Wing Morphometry and Acoustic Signals in Sterile and Wild Males: Implications for Mating Success in Ceratitis capitata - João Maria Gomes Alencar de Souza; Paulo Augusto de Lima-Filho; Wagner Franco Molina; Lúcia Maria de Almeida; Milson Bezerra de Gouveia; Francisco Pepino de Macêdo; Raul Alberto Laumann; Beatriz Aguiar Jordão Paranhos (The Scientific World Journal)
The sterile insect technique (SIT) is widely utilized in the biological control of fruit flies of the family Tephritidae, particularly against the Mediterranean fruit fly. This study investigated the interaction between mating success and morphometric variation in the wings and the production of acoustic signals among three male groups of Ceratitis capitata (Wiedemann): (1) wild males, (2) irradiated with Co-60 (steriles), and (3) irradiated (steriles) and treated with ginger oil. The canonical variate analysis discriminated two groups (males irradiated and males wild), based on the morphological shape of the wings. Among males that emit buzz signals, wild males obtained copulation more frequently than males in Groups 2 and 3. The individuals of Group 3 achieved more matings than those in Group 2. Wild males displayed lower pulse duration, higher intervals between pulses, and higher dominant frequency. Regarding the reproductive success, the morphological differences in the wings’ shape between accepted and nonaccepted males are higher in wild males than in the irradiated ones. The present results can be useful in programs using the sterile insect technique for biological control of C. capitata.